Differential regulation of synaptic plasticity of the hippocampal and the hypothalamic inputs to the anterior thalamus - O'MARA, SHANE MICHAEL (My University, 2009)
The hippocampus projects to the anterior thalamic nuclei both directly and indirectly via the mammillary bodies, but little is known about the electrophysiological properties of these convergent pathways. Here we demonstrate, for the first time, the presence of long-term plasticity in anterior thalamic nuclei synapses in response to high- and low-frequency stimulation in urethane-anaesthetized rats. We compared the synaptic changes evoked via the direct versus the indirect hippocampal pathways to the anterior thalamus, and found that long-term potentiation (LTP) of the thalamic field response is induced predominantly through the direct hippocampal projections. Furthermore, we have estimated that that long-term depression (LTD) can be induced only after stimulation of the indirect connections carried by the mammillothalamic tract. Interestingly, basal synaptic transmission mediated by the mammillothalamic tract undergoes use- dependent, BDNF-mediated potentiation, revealing a distinct form of plasticity specific to the diencephalic region. Our data indicate that the thalamus does not passively relay incoming information, but rather acts as a synaptic network, where the ability to integrate hippocampal and mammillary body inputs is dynamically modified as a result of previous activity in the circuit. The complementary properties of these two parallel pathways upon anterior thalamic activity reveal that they do not have duplicate functions
PUBLISHED